2020
DOI: 10.1101/2020.07.15.20147041
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A systematic review uncovers a wide-gap between COVID-19 in humans and animal models

Abstract: Background: Animal models of COVID-19 have been rapidly reported after the start of the pandemic. We aimed to assess whether the newly created models reproduce the full spectrum of humans COVID-19. Methods: We searched the Medline, as well as BioRxiv and MedRxiv preprint servers for original research published in English from January 1, to May 20, 2020. We used the search terms COVID-19 OR SARS-CoV-2 AND, animal models, hamsters, nonhuman primates, macaques, rodent, mice, rats, ferrets, rabbits, cats, and dog… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 89 publications
(243 reference statements)
0
3
0
Order By: Relevance
“…These limitations could be addressed with an appropriate animal model, replicating the pathogenesis of human COVID-19 [ 207 ]. However, although the mild COVID-19 phenotype and viral replication in the respiratory tract can be mimicked in non-human primates, hamsters, ferrets and cats, none of these animals features the cytokine storm and coagulopathy that characterizes severe COVID-19 in humans [ 208 ]. Therefore, this review primarily focused on SARS-CoV-2 studies in the context of humans.…”
Section: Discussionmentioning
confidence: 99%
“…These limitations could be addressed with an appropriate animal model, replicating the pathogenesis of human COVID-19 [ 207 ]. However, although the mild COVID-19 phenotype and viral replication in the respiratory tract can be mimicked in non-human primates, hamsters, ferrets and cats, none of these animals features the cytokine storm and coagulopathy that characterizes severe COVID-19 in humans [ 208 ]. Therefore, this review primarily focused on SARS-CoV-2 studies in the context of humans.…”
Section: Discussionmentioning
confidence: 99%
“…Of these readouts, the host response, as assessed by ViP signatures, is a key vantage point because an overzealous host response is what is known to cause fatality. Recently, a systematic review of the existing preclinical animal models revealed that most of the animal models of COVID-19 recapitulated mild patterns of human COVID-19; no severe illness associated with mortality was observed, suggesting a wide gap between COVID-19 in humans ( Spagnolo et al, 2020 ) and animal models ( Ehaideb et al, 2020 ). It is noteworthy that alternative models that effectively support viral replication, such as the proximal airway epithelium or iPSC-derived AT2 cells (analyzed in this work) or a fetal lung bud tip-derived organoid model recently described by others ( Lamers et al, 2021 ), do not recapitulate the host response in COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Of these readouts, the host response, as assessed by ViP signatures, is a key vantage point because an overzealous host response is what is known to cause fatality. Recently, a systematic review of the existing pre-clinical animal models revealed that most of the animal models of COVID-19 recapitulated mild patterns of human no severe illness associated with mortality was observed, suggesting a wide gap between COVID-19 in humans (Spagnolo et al, 2020) and animal models (Ehaideb et al, 2020). The model revealed here, in conjunction with the ViP signatures described earlier (Sahoo et al, 2020), could serve as a pre-clinical model with companion diagnostics to identify drugs that target both the viral and host response in pandemics.…”
Section: Discussionmentioning
confidence: 99%